Strategi Advokasi WWF dalam Menekan Perdagangan Gading Gajah Ilegal di Thailand Tahun 2013-2016 - Supraniti Sudharsana, Tjokorda Istri; Kumala Dewi, Putu Ratih; Prameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2019), 2019)
ABSTRACT Uncontrolled illegal elephant ivory trade has become an international issue. It causes a decline in the elephant population. Thailand is a country that still trades elephant ivory, even though it has ratified CITES. Legal uncertainty in Thailand, and the lack of attention to this issue, make the handling of illegal elephant ivory trade is still not optimal. This condition made WWF carry out several advocacy activities to help deal with the case. The locus of this study is 2013-2016, with the type of research is descriptive qualitative. This research uses the concepts of international norms, NGO advocacy roles, and NGO advocacy strategies and tactics. The results of the study illustrate that in this case, there were two strategies and tactics used by WWF in carrying out its advocacy role. The strategy is inside-outside strategy followed with inside-outside tactics. Keywords : WWF, Illegal elephant Ivory Trade, Inside-Outside Strategy, Inside-Outside Tactics.